2020
DOI: 10.5194/nhess-20-673-2020
|View full text |Cite
|
Sign up to set email alerts
|

High-accuracy coastal flood mapping for Norway using lidar data

Abstract: Abstract. Using new high-accuracy light detection and ranging (lidar) elevation data we generate coastal flooding maps for Norway. Thus far, we have mapped ∼80 % of the coast, for which we currently have data of sufficient accuracy to perform our analysis. Although Norway is generally at low risk from sea level rise largely owing to its steep topography and land uplift due to glacial isostatic adjustment, the maps presented here show that, on local scales, many parts of the coast are potentially vulnerable to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…But in low-lying coastal areas, storm surges have caused considerable damage to buildings and transport infrastructure in the past [41]. In the future there could be increased incidences, as model projections for Norway show an increase in storm surges and extreme water levels [35,37,38].…”
Section: Sea Level Rise and Extreme Water Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…But in low-lying coastal areas, storm surges have caused considerable damage to buildings and transport infrastructure in the past [41]. In the future there could be increased incidences, as model projections for Norway show an increase in storm surges and extreme water levels [35,37,38].…”
Section: Sea Level Rise and Extreme Water Levelsmentioning
confidence: 99%
“…Damage to infrastructure had 'Documented links' to 4 climate stressors (Sea level rise and extreme water levels, Storms, Extreme temperatures and heatwaves, Precipitation/runoff). Breeding and hatchery facilities are located close to the coast (Fig 1 ), and studies have shown that many Norwegian coastal areas are susceptible to flooding from storm surges due to sea level rise [40,41], which may cause damage to buildings and wider infrastructure. Storms are also known to cause destruction within affected areas, e.g.…”
Section: Breeding and Hatcherymentioning
confidence: 99%
“…The terminology of "coastal climate services" has just evolved throughout the last few years, with only a few studies referring to the specific term (Le Cozannet et al 2017, Hinkel et al 2019, Breili et al 2020, Khan et al 2020, Stephens et al 2020. All of those studies relate to adaptation to sea-level rise and predominantly address the physical aspect from a social perspective.…”
Section: Transformative Knowledgementioning
confidence: 99%
“…Webster et al [211] used topographic LiDAR to map the flood hazard from storm-surge events for Charlottetown on Prince Edward Island in Canada. Moreover, numerous research papers have been based on the use of high-density LiDAR data, often in combination with 2D streamflow hydraulic modelling using high-density LiDAR for mapping high accuracy urban, river or coastal flood risks [212][213][214][215]. Morrissey et al [216] used LiDAR data for modelling groundwater flooding in a lowland karst catchment.…”
Section: Flood Events and Floodplain Risksmentioning
confidence: 99%